1993
DOI: 10.1136/gut.34.12.1705
|View full text |Cite
|
Sign up to set email alerts
|

Location of tumour necrosis factor alpha by immunohistochemistry in chronic inflammatory bowel disease.

Abstract: This study determined the location and tissue

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
281
4
10

Year Published

1999
1999
2017
2017

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 498 publications
(304 citation statements)
references
References 40 publications
9
281
4
10
Order By: Relevance
“…[131][132][133] Relatives of subjects diagnosed with either Crohn's or psoriasis also have been shown to have an increased incidence of having the other disease. 134 Genetic [135][136][137][138] and pathologic [139][140][141][142] connections between these two diseases support these findings, and most recently both have been linked to specific gentotypes of IL-23. 143 Two studies have shown that psoriasis is more common in MS families than in controls.…”
Section: Other Immune-mediated Diseasesmentioning
confidence: 91%
“…[131][132][133] Relatives of subjects diagnosed with either Crohn's or psoriasis also have been shown to have an increased incidence of having the other disease. 134 Genetic [135][136][137][138] and pathologic [139][140][141][142] connections between these two diseases support these findings, and most recently both have been linked to specific gentotypes of IL-23. 143 Two studies have shown that psoriasis is more common in MS families than in controls.…”
Section: Other Immune-mediated Diseasesmentioning
confidence: 91%
“…Histamine content and its secretion have been found to be significantly increased particularly in affected mucosa of ulcerative colitis and Crohns disease compared with unaffected tissues [16,17]. Moreover, TNF-␣ concentrations are demonstrated to be markedly increased in the affected intestinal mucosa, serum, and feces of active inflammatory bowel diseases [18][19][20]. TNF-␣ and histamine induce rapid up-regulation of CD11b/CD18 on neutrophils, and P-selectin on endothelial cells and platelets, respectively, resulting in increased intercellular adhesion [23,24].…”
Section: Introductionmentioning
confidence: 95%
“…Because inflammatory cytokines such as IL-8 and TNF-␣ are detected in the lesions of inflammatory bowel diseases [19,20,39], these cytokines are assumed to affect neutrophil adhesion to intestinal epithelial cells by modulating expression of neutrophil adhesion molecules. As shown in Figure 7, pretreatment of neutrophils with IL-8 or TNF-␣ increased neutrophil adhesion to both resting and TNF-␣ (5 h and 30 min)-or histamine (30 min)-stimulated HT29 cells (1.3ϳ2.5-fold).…”
Section: Effect Of Neutrophil Stimulation On Neutrophil Adhesion To Hmentioning
confidence: 99%
“…IBD patients have elevated levels of TNF and COX-2 in the epithelial cell layer of the GI tract (40,46,62). However, the biological and pathological consequences of COX-2 in the context of elevated TNF levels in normal colon epithelial cells are not well known.…”
Section: Cox-2 Protects Against Tnf Cytotoxicity In Colon Epithelialmentioning
confidence: 99%